Optimisation of surface topography characterisation for metal additive manufacturing using coherence scanning interferometry - Gómez, Carlos A.; Su, Rong; Thompson, Adam; DiSciacca, Jack; Lawes, Simon; Leach, Richard K. (2017)
The surface topography of metal additive manufactured (AM) parts can be challenging to measure due to the presence of complex features, such as high slopes, step like recesses and protuberances, and local variations in reflectance. Recent innovations in coherence scanning interferometry (CSI) technology, such as high dynamic range of exposure and adjustable data acquisition rates for noise reduction, have augmented the baseline sensitivity of a measurement. This enhanced sensitivity expands the capability of CSI instruments to measure surface textures with high slopes or low reflectance, making CSI a potentially valuable tool for process development and quality control of metal AM. This study presents an empirical sensitivity analysis of a CSI system for the top and side surfaces of metal AM parts made from different materials (Ti-6Al-4V and Al-Si-10Mg) and processes (laser powder bed fusion (LPBF) and electron beam powder bed fusion (EBPBF)). The aim of this work is to demonstrate the feasibility of using CSI for characterisation of metal AM surfaces, and to evaluate the effectiveness of relevant CSI measurement settings. Topographic measurements are described through the use of ISO 25178-2 areal surface texture parameters Sq and Sdq and are analysed for data coverage, measurement time and area. The results show that the CSI technique can provide surface topography measurements for metal AM surfaces with a wide range of surface features. Finally, recommendations for optimisation of future measurements on metal AM surfaces using CSI are provided.